Ultrasound-promoted synthesis of novel dihydropyrido[2,3-d:5,6- d`]dipyrimidine derivatives - Mamaghani, Manouchehr (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
An efficient synthesis of dihydropyrido[2,3-d:5,6-d`]pyrimidine derivatives was developed via one-pot three-component reaction of 6-amino-2-(alkylthio)-pyrimidine-4(3H)one and aryl aldehydes in the mixed solvent of glacial acetic acid and DMF (1:1, v:v) under ultrasonic irradiation. In this protocol novel fused dihydropyrido[2,3-d]pyrimidines were synthesized in high yields (80-97%) and lower reaction times (5-25 min).